Spatial Variation of Surface Water Quality at Gebeng Industrial Estate, Pahang, Malaysia - Hossin, Amjed; Islam, Mir Sujaul; Nasly, Mohamed Ali; Zularisam, A. W.; Edriyana, Abd Aziz (2012)
Gebeng is the main industrial area of Pahang, where, Tunggak is a strategic river. The anthropogenic impact on the river is as a result of rapid industrialization in Gebeng. This river is of particular importance in the study of surface water quality status because effluents from industries of Gebeng discharge into it thereby deteriorating the quality. Water quality parameters were analyzed across the river with the objective to disclose the spatial variation of the river water quality. To conduct the study, water samples were collected monthly from 10 sampling station across the river basin. The physicochemical parameters were analyzed using APHA & HACH standard methods as well as the trace elements were determined using ICP-MS (Inductively Coupled Plasma Mass Spectrometry). Data analyses were done using SPSS statistical software. The study revealed that, pollution from non-point source was associated with runoff from construction sites of newly developed industrial areas and the point source contributing the major pollutants especially from industrial wastes. According to Interim National Water Quality Standard (INWQS) based on DO, COD, ammoniacal nitrogen and some selected trace elements, major part of the river specially the mid-region was categorized as class V (very highly polluted) while some part was found in class IV (highly polluted) and rest of class III (polluted) as well. Furthermore, classification of the river based on DOE-WQI showed that seven (7) stations (2-8) were in class IV (highly polluted); station 1, 9 & 10 were found to be polluted. So, from the study it is concluded that pollution is higher in the middle stations of the river compared to the upper and lower stream. This was due to less industry at upper stream and the tidal interference was present in lower stream and obviously the industrial wastes were mixing in the middle stations most.